Isolation and Enrichment of Rat Mesenchymal Stem Cells (MSCs) and Separation of Single-colony Derived MSCs - Zhang, Linxia (MyJove Corporation, 2010)
MSCs are a population of adult stem cells that is a promising source for therapeutic applications. These cells can be isolated from the bone marrow and can be easily separated from the hematopoietic stem cells (HSCs) due to their plastic adherence. This protocol describes how to isolate MSCs from rat femurs and tibias. The isolated cells were further enriched against two MSCs surface markers CD54 and CD90 by magnetic cell sorting. Expression of surface markers CD54 and CD90 were then confirmed by flow cytometry analysis. HSC marker CD45 was also included to check if the sorted MSCs were depleted of HSCs. MSCs are naturally quite heterogeneous. There are subpopulations of cells that have different shapes, proliferation and differentiation abilities. These subpopulations all express the known MSCs markers and no unique marker has yet been identified for the different subpopulations. Therefore, an alternative approach to separate out the different subpopulations is using cloning cylinders to separate out single-colony derived cells. The cells derived from the single-colonies can then be cultured and evaluated separately.